2019
DOI: 10.1038/s41416-019-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase II trial of mFOLFOX6 plus bevacizumab versus mFOLFOX6 plus cetuximab as first-line treatment for colorectal liver metastasis (ATOM trial)

Abstract: BackgroundChemotherapy with biologics followed by liver surgery improves the resection rate and survival of patients with colorectal liver metastasis (CRLM). However, no prospective study has compared the outcomes of chemotherapy with bevacizumab (BEV) versus cetuximab (CET).MethodsThe ATOM study is the first randomised trial comparing BEV and CET for initially unresectable CRLM. Patients were randomly assigned in a 1:1 ratio to receive mFOLFOX6 plus either BEV or CET. The primary endpoint was progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…After study treatment followed by surgical resection of tumors with R0/R1 status, the median progression-free survival of the bevacizumab-treated arm was 6.5 months [95% con dence interval (CI) = 4.0-13.6 months], whereas that of the cetuximab-treated arm was 13.8 months (95% CI = 8.4 months-not reached; hazard ratio = 0.610, 95% CI = 0.298-1.245). Of the 57 tumors for which the histopathological analysis was assessable, the histopathological response rate (grade 1b/2/3) was 66.6% (20/30) in the bevacizumab-treated arm and 92.6% (25/27) in the cetuximabtreated arm (p = 0.0229) (16), indicating that the rate tended to be better in the cetuximab-treated arm (21).…”
Section: Discussionmentioning
confidence: 99%
“…After study treatment followed by surgical resection of tumors with R0/R1 status, the median progression-free survival of the bevacizumab-treated arm was 6.5 months [95% con dence interval (CI) = 4.0-13.6 months], whereas that of the cetuximab-treated arm was 13.8 months (95% CI = 8.4 months-not reached; hazard ratio = 0.610, 95% CI = 0.298-1.245). Of the 57 tumors for which the histopathological analysis was assessable, the histopathological response rate (grade 1b/2/3) was 66.6% (20/30) in the bevacizumab-treated arm and 92.6% (25/27) in the cetuximabtreated arm (p = 0.0229) (16), indicating that the rate tended to be better in the cetuximab-treated arm (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CET is a monoclonal antibody directed against the epidermal growth factor receptor, which can improve OS and PFS in patients with CRC and maintain a quality of life for patients (Jonker et al, 2007). Oki et al (Oki et al, 2019) believed that liver metastases are less than or equal to 4 and larger than 5 cm in diameter, which is a good indicator for the use of CET for initially unresectable CRLM. However, Karapetis et al (Karapetis et al, 2008) showed that patients with CRC bearing wild-type KRAS did benefit from CET, whereas those bearing mutated KRAS did not.…”
Section: Discussionmentioning
confidence: 99%
“…During follow up of patients treated by surgical resection of tumors with R0/R1 status, the median PFS of the bevacizumabtreated group was 6.5 months (95% CI=4.0-13.6), whereas in the cetuximab arm it was 13.8 months (95% CI=8.4-not reached), HR=0.610 (95% CI=0.298-1.245). Of the 57 tumors for which the histopathological analysis was assessable, the Grade 1b/2/3 histopathological response rate was 66.6% (20/30) in the bevacizumab arm and 92.6% (25/27) in the cetuximab arm (p=0.0229) (20).…”
Section: Egfr Therapy Heat Map (A) and Analysis Matrix (B) Of The Comentioning
confidence: 99%
“…Recently, the multicenter, randomized phase II ATOM trial was performed to evaluate the efficacy and safety of mFOLFOX6+bevacizumab and mFOLFOX6+cetuximab in patients suffering liver-limited metastasis from wild-type all-RAS CRC (20). As assessed by the independent review committee, the median PFS for the cetuximab arm was 14.8 months [95% confidence interval (CI)=9.7-17.3 months], whereas that for the bevacizumab arm was 11.5 months (95% CI=9.2-13.3 months; log-rank p=0.33).…”
Section: Egfr Therapy Heat Map (A) and Analysis Matrix (B) Of The Comentioning
confidence: 99%